"Modlitwa dla Marty" - pieśń dwóch rewolucji - Skobrtal, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This paper focuses on the legendary song entitled Prayer for Marta and its performer. It is a history of two revolutions and a famous singer’s difficult life. Both were the symbols of changes in Czechoslovakia. Both were absent in a public life as the song was banned and Marta Kubišová couldn’t perform. Nowadays, both are the icons of modern Czech history. This article describes how this song was created and sang twice. It also explains who was its author. What is more, Marta ‘s life and her view on contemporary politics are presented.